Post-Yugoslav theatre of memory in the visual projects of Bálint Szombathy and Jasmina Cibic - Bogusławska, Magdalena (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The starting point of my considerations is the category of the theatre of memory, taken from Francis Yates’ book Art of memory. The category was applied in the book in relation to ancient traditions and mnemonic techniques. In the article I attempt to reinterpret this category and apply it in the description of the contemporary practices of commemorating and reminding of the Socialist Yugoslavia’s experience in space and through space. I am interested in the artistic activities of contemporary visual creators who in their works deal with the subject of SFRY. Referring to the example of the works of the artists belonging to different generations, I discuss two trends seen in the reception of this historical experience. Metonymic approach (Szombathy) is based on problematizing one’s own biographical experience as a part of the G reat H istory, while the metaphorical recognition (Cibic) means a search for universal content in what is historical and local.